Improved outcome of acute myeloid leukaemia in Down's syndrome. - Craze, J; Harrison, G; Wheatley, K; Hann, I; Chessells, J (1999)
OBJECTIVE: To review the clinical features, treatment, and outcome of children in the UK with Down's syndrome and acute myeloid leukaemia (AML). DESIGN: A retrospective study of 59 children with Down's syndrome and AML presenting between 1987 and 1995. Data were obtained from hospital case notes, trial records, and by questionnaire. RESULTS: The patients were unusually young (median age, 23 months) with a predominance of megakaryoblastic AML. Two of the seven infants who presented with abnormal myelopoesis aged 2 months or younger achieved complete spontaneous remission. Most of the older children with AML (32 of 52) were treated on recognised intensive protocols but 13 received individualised treatment and seven symptomatic treatment alone. Only four received a bone marrow transplant (BMT) in first remission. For the 45 older children who received chemotherapy the overall survival was 55% (median follow up 4.5 years). Patients on individualised protocols had a similar overall survival and toxic death rate but marginally higher relapse rate than those on standard (intensive) protocols. Children with Down's syndrome treated on the national AML 10 trial had a similar overall survival (70% v 59%) at five years to children of comparable age without Down's syndrome: their improved relapse risk (12% v 38%) offset the slight increase in deaths as a result of treatment toxicity (19% v 11%). CONCLUSION: Neonates with Down's syndrome and abnormal myelopoesis may achieve spontaneous remission, and older children with Down's syndrome and AML can be treated successfully with intensive chemotherapy, without BMT.